Motivational Factors That Contribute Motivational Factors That Contribute To The Malay Students' Academic Performances At Selected Public And Private Universities - Abu Hassan, Badrolhisham (2008)
The Malay students' performance has been deemed unsatisfactory by several Malay leaders. This study investigates the intrinsic and extrinsic motivational factors that affect the students' performance at selected public and private universities and the impact of demographic motivational factors on the students' performance.